Hedging with the IFOX Long Gilt Future: A note - Hogan, John (Economic & Social Studies, 1990)
Traditional theory emphasises the risk avoidance potential of futures. An alternative hypothesis (Working's hypotheses) emphasised expected profit maximisation. Portfolio theory is a combination of the first two hypothesis, focusing on risk return characteristics of futures, helping explain the coexistence of hedged and unhedged portfolios. The purpose of this paper is to examine the efficiency of using the IFOX long gilt future as a hedge against exposure in the cash market to medium and long dated Irish Government stocks. The relative efficiency of different hedge ratios is also examined.
Keywords: hedging; IFOX; long gilt fures